1997
DOI: 10.1139/b97-919
|View full text |Cite
|
Sign up to set email alerts
|

Puccinia recondita causing leaf rust on cultivated wheats, wild wheats, and rye

Abstract: Aecial and telial host range, interfertility, teliospore dimensions, and amount of nuclear DNA were determined for Puccinia recondita collected either worldwide from species of cultivated wheats (Triticum aestivum and Triticum turgidum ssp. durum and rye (Secale cereale), or from wild emmer (Triticum turgidum ssp. dicoccoides) and four species of wild wheat (Aegilops) in Israel. The results indicate that the collections belong in two major groups: Group I (from cultivated wheats and wild emmer), which has Thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 4 publications
0
44
0
6
Order By: Relevance
“…While these genes are effective against Puccinia triticina (formerly P. recondita f. sp. tritici; Anikster et al 1997) no information is available on whether they are also effective against P. recondita f. sp. secalis in rye.…”
Section: Discussionmentioning
confidence: 99%
“…While these genes are effective against Puccinia triticina (formerly P. recondita f. sp. tritici; Anikster et al 1997) no information is available on whether they are also effective against P. recondita f. sp. secalis in rye.…”
Section: Discussionmentioning
confidence: 99%
“…Puccinia triticina Erikss (Anikster et al, 1997), a causal agent of leaf rust, is the most widely distributed and frequently occurring wheat pathogen in the world. Leaf rust is common in South America, and under favorable environmental conditions, it can cause significant damage to most wheat cultivars grown in this region (Bjarko et al, 1988;Barcellos et al, 2000;Huerta-Espino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The recent morphological and genetic studies of the pathogen showed that P. recondita is not the incitant of wheat leaf rust rather P. triticina should be the preferred name as shown by Savile (1984) and Anikster et al (1997). Although, stripe rust disease of wheat was first described by Gadd in 1777 but Schmidt (1827) named the stripe rust fungus as Uredo glumarum.…”
Section: Pathogen: Taxonomy Symptomsmentioning
confidence: 99%